(untitled) (Mediscope, 2018)
We conducted a comparative study on sixty full-term newborn babies with cerebral edema and severe perinatal asphyxia treating with mannitol or dexamethasone in Ad-din Sakina Medical College Hospital, Jessore. The age (in hours) of the children in both groups was similar. The score for clinical condition of the children with perinatal asphyxia at 24 hours, 48 hours and 72 hours after using mannitol were significantly lower than the respective score at 24 hours, 48 hours and 72 hours after using dexamethasone (p < 0.01, p < 0.05 and p < 0.001, respectively). The score for bulging condition of anterior fontanelle of the children with perinatal asphyxia at 24 hours, 48 hours and 72 hours after using mannitol were significantly lower than the respective score at 24 hours, 48 hours and 72 hours after using dexamethasone (p < 0.05, p < 0.05 and p < 0.001, respectively). The score for clinical condition of the children with perinatal asphyxia at 24 hours, 48 hours and 72 hours after using mannitol were significantly lower than the respective score before the treatment (p < 0.05, p < 0.001 and p < 0.001, respectively). The scores at 48 hours and 72 hours after using dexamethasone were significantly lower than the respective score before the treatment (p < 0.001 and p < 0.001, respectively). The score for bulging condition of anterior fontanelle of the children with perinatal asphyxia at 24 hours, 48 hours and 72 hours after using mannitol were significantly lower than the respective score before the treatment (p < 0.001, p < 0.001 and p < 0.001, respectively). The score at 48 hours and 72 hours after using dexamethasone were significantly lower than the respective score before the treatment (p < 0.001 and p < 0.001, respectively). Mannitol seems to be more beneficial than dexamethasone in the management of severe perinatal asphyxia due to raised intracranial pressure associated with cerebral edema. Mediscope Vol. 5, No. 2: Jul 2018, Page 16-20